ANALISIS KETERSEDIAAN MEDIA PEMBELAJARAN PADA SATUAN PENDIDIKAN DI SUNGAI JAMBUR - Nofrion; Sandia Friska; Nurma Indah; Rafi Septian Rizki; Viola Zeli Andini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the availability, condition, and utilization of learning media in educational institutions in Nagari Sungai Jambur. The research employed a descriptive approach with direct observation as the primary data collection technique. Observations were conducted in several schools to identify the types of learning media available, their condition, and their use in the learning process. The results showed that the available learning media consisted of print media, visual media, and technology-based media. Print media, such as textbooks, modules, and student worksheets, were the most widely available and frequently used. Visual media, including pictures, posters, maps, and teaching aids, were also utilized to support students’ understanding of learning materials. Meanwhile, technologybased media, such as laptops and televisions, were available in some schools; however, their use remained limited due to the lack of equipment and insufficient user skills. In general, the condition of the learning media was relatively good and suitable for classroom use. Nevertheless, several challenges were identified, including an insufficient number of textbooks, minor damage to teaching aids, and less-than-optimal media management. The use of learning media was found to enhance students’ attention, participation, and understanding during the learning process. Therefore, efforts are needed to improve the quantity, quality, and variety of learning media to support more effective and engaging learning activities and to achieve educational objectives more optimally.